PERTANGGUNGJAWABAN HUKUM FINTECH LENDING ATAS KREDIT MACET DALAM PERJANJIAN ELEKTRONIK - Rahmat Giling; Hasnah Aziz; Nursalim; Mahmuddin; Dany Wahyu (Berajah Journal, 2026)
The development of financial technology lending (fintech lending) in Indonesia has transformed the financing landscape by introducing electronic agreements as the primary legal instrument in creditor-debtor relationships. However, the increasing volume of non-performing loans in this sector raises fundamental questions regarding the legal accountability of fintech lending providers. This article aims to analyze juridically the legal accountability of fintech lending for non-performing loans arising from electronic agreements. The research method used is qualitative with a normative-empirical legal approach. Data was collected through studies of legislation, court decisions, Financial Services Authority reports, and scientific literature studies. The results show that the legal accountability of fintech lending for non-performing loans involves three crucial aspects: first, the legal status of fintech lending as an intermediary versus a party to the credit agreement; second, the distribution of responsibility among fintech lending, partner banks, and investors in the peer-to-peer lending financing structure; and third, the mechanism for resolving non-performing loans that fulfills the principle of substantive justice. This article recommends the need for clarification of the legal status of fintech lending in legislation, harmonization of obligations among parties in electronic agreements, and development of a proportional non-performing loan resolution mechanism.